PENGARUH LINGKUNGAN BELAJAR DI SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA SMK MANDIRI PONTIANAK - Hermansyah, Hermansyah; Sulistyarini, Sulistyarini; Genji, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis entitled "the influence of learning environment in school toward the students’learning motivation at SMK Mandiri Pontianak" common problem in this research is "whether there is influence of learning environment in school to the students’ learning motivation at SMK Mandiri Pontianak". The method used in this research is descriptive method in the form of correlation studies. The populations in this study were all students of class XI and XII which amounted to 230 students, the sample taken using random sample totaling 146 students. Data collection used questionnaire / questionnaire techniques, and documentation techniques. The results showed that there is influence between independent variable (X) to the dependent variable (Y) which is known through the calculation by using simple linear regression equation formula Y = a + bX then it is shown in Y = 9,615 + 0,858X which means the value of constant is 9,615 if the learning environment (X) is 0 (zero), then the learning motivation (Y) is worth 9,615. The regression coefficient value of the learning environment variable (X) is 0.858. This means that every improvement of learning environment (X) is 1, then the learning motivation (Y) will increase by 0.858 and test the t test hypothesis> t table, because the value of t arithmetic> t table is 20.650> 1.976 then Ha accepted and Ho rejected or "there is influence of learning environment in school to students’ motivation learning at SMK Mandiri Pontianak". Keywords: Environment Learning, Motivation Learning